Minimal Invasive Surgical Management of Familial Arteriovenous Malformation - Mokhtar Mamdouh Abdel-Latif; Shankargouda Patil (Case Reports in Dentistry)
Introduction. Familial arteriovenous malformations are exceedingly rare. They are often noted at birth. They can also present during childhood or adolescence. Sclerotherapy has proven to have a favorable outcome. Case Presentation. The present case report describes the treatment of arteriovenous malformations on the tongue, labial mucosa, and vermilion border in siblings treated with boiling saline injections. Conclusion. Sclerotherapy using boiling saline had shown to effectively treat arteriovenous malformations in the oral region without any significant morbidity.